فاعلية برنامج تدريبي لتنمية بعض المهارات الاجتماعية لدى الاطفال المصابين باضطراب طيف التوحد - كير, آية; بده زكري, نرجس (University of Eloued جامعة الوادي, 2023)
Study Summary The current study aims to verify the effectiveness of a training program for the development of certain social skills (social literature and social participation) in children with autism spectrum disorder. The study relied on the semi-experimental approach by designing one group with three measurements: before, after and tracking using the scale Estimation of social skills for: Magdi Ghazal (2007), where the experimental group was selected intentionally, and it was estimated at: 7 male children with autism spectrum disorder to a moderate degree, the sessions of the proposed training program for the development of social skills were applied to the study sample, after collecting the study data and processing them statistically, the study concluded the following results: 1_There are statistically significant differences in the level of social skills among the members of the study sample between the pre-measurement and the post-measurement in favor of the post-measurement 2_There are no statistically significant differences in the level of social skills among the members of the study sample between telemetry and tracer measurement.
دراسة ميدانية بجمعية أمل بالمقرن - الوادي
مذكرة ماستر في علوم التربية تخصص تربية خاصة تعليم مكيف
Keywords: المهارات الإجتماعية، compétences sociales, social skills; التوحد، Autisme, Autism